Trajetos formativos de docentes de libras do ensino superior: dentre saberes e representações - Corrêa, Lucinara Bastiani (2017)
This work describes the research performed with Libras (Brazilian sign language) professors from two college institutions in Rio Grande do Sul, Brazil, aiming to realize how this professional is constituted, throughout their formative journey, besides comprehending how these journeys influenced the pedagogical praxis from these professionals. Thereby, I aimed to know the formative journey from Libras professors who work in college institutions; realizing some knowledge and necessary dispositions for the Libras teaching in the perception of these professionals; in addition, verify the teaching significations from these professionals. Therefore, a qualitative research was methodologically developed throughout oral narratives. For the data collection, individual interviews were performed, from the semi-structured type with the professors, also questioning about their practices, in order to foment the narrated data triangulation with their planning and implementation. The data analysis was organized under the assumptions of the Categorial Thematic Content Analysis. Interviews were performed with deaf and hearing Libras professors from two college institutions. Constitutive elements of teaching identity of each professor are present in their narratives, delimiting the intrinsic relation between personality and professionality, considering that when describing themselves as professors they also do it as people, or vice-versa. In relation to wisdom or disposition for teaching mobilized in pedagogical praxis, the professors consider, unanimously, in first place the Libras specific knowledge, education, history, culture and deaf identities; followed by working context appropriation; pedagogical awareness and by methodological and didactic matters. When regarding formative journeys it is realized that these cross each other in determined formation locations, even in distinct times, also delimiting the absence of alternatives for permanent formation aiming for the qualification of their actions while Libras teachers, demanding alternative search processes with the institution colleagues, since they emphasize the understanding of formation as a continuum. It was also possible to perceive the existence of emergent tensions related to the occupation of LIBRAS teachers’ work between deaf and listeners subjects.